Natural convection in a cavity under partial magnetic field applied from different corners - Geridonmez, B. Pekmen; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
In this study, natural convection in a differentially heated square cavity is investigated under the influence of a partial uniform magnetic field applied from either the left bottom corner of the heated wall or the right bottom corner of the cold wall. The governing dimensionless equations are numerically solved by thin plate spline radial basis functions (Rbf) based pseudo spectral method. Relevant parameter variations, Hartmann and Rayleigh numbers, the lengths of the left or right bottom corners of the partial magnetic field and the angle of the applied magnetic field are analyzed in terms of streamlines, isotherms and vorticity contours as well as average Nusselt number through the hot wall. The inhibition of Lorentz force is realized if the corner partial magnetic field of length less than a half is applied from the left bottom corner at Ra = 10(5) and Ha = 50. In addition, in case of the applied magnetic field from the left bottom corner, the average Nusselt number and the maximum absolute value of the stream function also decrease 8.49% and 5.85%, respectively, more than the applied magnetic field from the right bottom corner at Hartmann number of 100 and Rayleigh number of 10(6).
Keywords: Corner partial magnetic field; Natural convection; Radial basis functions; Thin plate splines